Nelson Mandela - Kramer, Barbara (Washington, D.C. : National Geographic, 2014)
Looks at the life and accomplishments of Nelson Mandela, a South African political activist who was imprisoned for his rebellion against racial segregation and was later elected as the first black president of South Africa.
Horn Book, April 2015
Includes index.
4.3
K-3
K-3
Horn Book
Keywords: Mandela, Nelson, -- 1918-2013 -- Juvenile literature; Presidents -- South Africa -- Biography -- Juvenile literature; Mandela, Nelson, -- 1918-2013.; Presidents; Blacks -- South Africa -- Biography; Mandela, Nelson, -- 1918-2013; Presidents -- South Africa -- Biography; Blacks -- South Africa -- Biography